Dissent and Philosophy in the Middle Ages Dante and His Precursors. - Fortin, Ernest L.; LePain, Marc A. (Lanham : Lexington Books, 2002)
Dissent and Philosophy in the Middle Ages offers scholars of Dante's Divine Comedy an integral understanding of the political, philosophical, and religious context of the medieval masterwork. First penned in French by Ernest L. Fortin, one of America's foremost thinkers in the fields of philosophy and theology, Dissidence et philosophie au moyen-%ge brings to light the complexity of Dante's thought and art, and its relation to the central themes of Western civilization. Available in English for the first time through this superb translation by Marc A. LePain, Dissent and Philosophy will make a.
Title Page; Copyright Page; Contents; Foreword; Introduction; Chapter 1 On the Political Mode in Philosophy; Chapter 2 Islam and the Rediscovery of Political Philosophy; Chapter 3 Political Philosophy in the Christian World; Chapter 4 Dante and Philosophical Allegory; Chapter 5 The Imperialism of the Comedy; Chapter 6 Dante and Christianity; Chapter 7 The Theory of the Double Truth; Chapter 8 The Decline of Political Philosophy; Appendix: Dante's Comedy As Utopia; Index; About the Author and Translator
Description based upon print version of record.
Keywords: Dante Alighieri, 1265-1321 -- Philosophy; Philosophy, Medieval; Dante Alighieri, -- 1265-1321 -- Philosophy; Philosophy, Medieval; POETRY / Continental European; Electronic books